2016
DOI: 10.1016/j.jceh.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Tackling the Hepatitis C Disease Burden in Punjab, India

Abstract: Hepatitis C virus (HCV) is a globally prevalent pathogen and is a major cause of healthcare burden in India. HCV poses a significant problem in the state of Punjab, India owing to the higher prevalence of risk factors like unsafe medical practices (including unsafe injections and dental procedures) and intravenous drug use. The reported prevalence of HCV in this part of the country was 5.2% in 2012, while a recent study has shown the prevalence to be 3.2% in 2016. Similar to the other geographic belts in India… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 37 publications
1
43
1
Order By: Relevance
“…According to the current study HCV GT3a (68.07%) and GT1a (25%) were predominant GTs circulating in UP, North India. The findings were in concordance with previous studies conducted in other states of north India, for example, Delhi, Haryana, and Punjab . The current study, reported HCV GT4a, which was not earlier reported from UP, India.…”
Section: Discussionsupporting
confidence: 93%
“…According to the current study HCV GT3a (68.07%) and GT1a (25%) were predominant GTs circulating in UP, North India. The findings were in concordance with previous studies conducted in other states of north India, for example, Delhi, Haryana, and Punjab . The current study, reported HCV GT4a, which was not earlier reported from UP, India.…”
Section: Discussionsupporting
confidence: 93%
“…25 Communitybased seroprevalence studies have mostly reported similar results, 26,27 but in some areas such as Punjab state, higher prevalence of 3·2-5·2% has been reported. 28,29 In a survey of 14 481 people who inject drugs, the weighted anti-HCV prevalence was 37·2% (including 13·2% with HCV-HIV co-infection), varying from 4·9% to 64·9% across 15 Indian cities. 30 Indirect evidence suggests that most cases of HCV infection are related either to unsafe injection practices or transfusion of contaminated blood or blood products before the introduction of mandatory testing of donated blood.…”
Section: Viral Hepatitis Hepatitis B D and Cmentioning
confidence: 99%
“…We were unable to correct the overall prevalence estimate to account for the prevalence among these populations due to a lack of data. A cross-sectional serosurvey asking about recent behaviours cannot accurately capture the effect of lifetime medical exposures and injections with contaminated needles, which are important factors associated with HCV prevalence in India, South Asia and globally [15, 34]. The receipt of medical injections is very common in this population, with around 35% of the sample having received one in the previous 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggest low socio-economic status (S-ES) is associated with increased HCV infection risk from healthcare exposures, such as re-use of syringes [14], which is a common practice in neighbouring Pakistan and has also been identified as a risk factor associated with increased odds of HCV in Punjab, India [15]. A combined, continuous S-ES score variable was created to increase power and better capture S-ES than individual variables.…”
Section: Methodsmentioning
confidence: 99%